Numerical research on relationship between flow pattern transition and condensation heat transfer in microchannel. Issue 5 (1st July 2014) - Sun, Dongliang; Xu, Jinliang; Ding, Peng
Abstract : Purpose: – Based on the numerical research on the relationship between the flow pattern transition and the condensation heat transfer in circular microchannels, the purpose of this paper is to bring forward a concept of external separation circular microchannel to regulate and control the flow pattern for enhancing the condensation heat transfer. Design/methodology/approach: – The numerical research is based on the volume of fluid method and the vapor-liquid phase change model proposed by the present authors. Findings: – By numerical research on the condensation process of water in a general circular microchannel, it is discovered that, with the increase of the inlet velocity and the reduction of the temperature difference between the saturation temperature and the channel wall temperature, the bubble detachment frequency is raised and the water vapor condensation length is extended, representing an exponential growth. Therefore, for the condensation process with low temperature difference and high mass flow rate, it is in urgent need to regulate and control the flow pattern. Originality/value: – To prevent the flow pattern in the general circular microchannel converted from annular flow to slug flow and then to bubble flow, this paper brings forward a concept of external separation circular microchannel, which regulates and controls the flow pattern by discharging partial liquid from the annular wall opening. After regulation and control, the flow pattern is converted from original periodic annular flow/slug flow/bubble flow to current stable annular flow. Accordingly, the heat transfer performance is enhanced and the condensation length is lowered remarkably.